A nondestructive method based on absorption of polychromatic neutron beam for monitoring internal gas of sealed container - Xinxi Li; Bo Li; Yun Wang; Liang Chen; Xiaoling Xiong; Jie Chen; Lin Zou; Chaoqiang Huang; Dong Liu (Nuclear Analysis)
Current work introduces a non-destructive testing method for evaluating the gas retention and internal pressure of sealed containers. Pulsed polychromatic neutrons of time-of-flight (TOF) neutron reflectometer Diting at the China Mianyang research reactor (CMRR) were utilized as the probe. By analyzing the transmitted neutron spectrum and employing an inversion fitting technique, the internal gas pressure with high accuracy up to 3 % can be determined. This method capitalizes on the large absorption cross-section of 3He gas, which provides the sensitivity required for detecting minute changes. The high intensity of the transmitted neutron beam enables rapid data collection, facilitating in situ measurement. The technique offers a direct measure of the gas pressure within sealed containers, which is significant for applications requiring quality control and safety measures, such as inertial confinement fusion (ICF) target pellet development and other non-destructive testing in various industries where the integrity and performance of sealed systems are paramount.